(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article evaluates the functional state of the thyroid gland (TG) in women with metabolic syndrome through hormonal examinations, as well as pathological changes in the TG tissue using ultrasound and histological analysis. According to the results obtained, an increase in thyroid volume was observed in Group 1 (150 women with metabolic syndrome) compared to the control group: Grade I goiter was recorded in 37.3% of cases, and Grade II goiter in 62.7% of cases. Analysis of the functional state of the TG confirmed that cases of subclinical and overt hypothyroidism were significantly higher in women of Group 1 compared to Group 2 (women without metabolic syndrome).